2006
DOI: 10.1158/1055-9965.epi-05-0710
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Important Role of Alcohol- and Aldehyde-Metabolizing Genes in Cancers of the Upper Aerodigestive Tract

Abstract: Background: Incidence and mortality rates of upper aerodigestive tract cancers in Central Europe are among the highest in the world and have increased substantially in recent years. This increase is likely to be due to patterns of alcohol and tobacco consumption. Genetic susceptibility to upper aerodigestive tract cancer in relation to such exposures is an important aspect that should be investigated among populations in this region. Methods: A multicenter case-control study comprising 811 upper aerodigestive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
106
0
12

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(135 citation statements)
references
References 30 publications
17
106
0
12
Order By: Relevance
“…However, further analyses in the rs1573496 (ADH7) polymorphism showed that alcohol intake was associated with CRC risk among heterozygous and homozygous carriers of the rare rs1573496(C) (ADH7) allele, while among homozygous wild-type participants the alcohol CRC association was weak. With respect to SNPs in the ALDH family, similar genes alcohol interactions have been previously observed for upper aero-digestive tract cancer, 21 for head and neck cancer, 31 and for CRC. 15 The alleles encoding the different ADH variants are heterogeneously distributed among ethnic groups.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…However, further analyses in the rs1573496 (ADH7) polymorphism showed that alcohol intake was associated with CRC risk among heterozygous and homozygous carriers of the rare rs1573496(C) (ADH7) allele, while among homozygous wild-type participants the alcohol CRC association was weak. With respect to SNPs in the ALDH family, similar genes alcohol interactions have been previously observed for upper aero-digestive tract cancer, 21 for head and neck cancer, 31 and for CRC. 15 The alleles encoding the different ADH variants are heterogeneously distributed among ethnic groups.…”
Section: Discussionsupporting
confidence: 72%
“…33 For alcohol-related cancers, an increased risk of upper aero-digestive tract cancers has been observed consistently in studies conducted in Europe 21,34 and in Japan. 35 For CRC, no clear explanation for the increased risk associated with the slow alcohol metabolizer rs1229984(G) (ADH1B) allele observed in Asian populations 15,16 has been provided.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…17 1 1 0 0 1 1 1 0 1 0 Cui et al 18 1 1 1 0 1 1 1 0 1 1 Dikshit and Kanhere 19 1 0 1 0 1 1 1 0 1 1 Elahi et al 20 1 1 1 0 1 1 1 1 1 1 Elwood et al 21 1 1 0 0 1 1 1 0 1 1 Franceschi et al 22 1 1 0 0 1 1 1 1 1 0 Franceschi et al 23 1 0 0 0 1 1 0 1 1 1 Franco et al 24 1 1 0 0 1 1 1 0 1 0 Greenberg et al 25 0 0 1 0 1 1 1 1 1 1 Guneri et al 26 0 1 0 0 1 1 0 0 1 0 Hashibe et al 27 1 1 0 0 1 1 1 0 1 1 Hayes et al 28 1 1 1 0 1 1 1 1 1 1 Herrero et al 29 1 1 0 0 1 1 1 1 1 1 Kabat et al 30 0 1 0 0 1 1 1 0 1 0 Ko et al 31 1 0 0 0 1 1 1 0 1 0 Levi et al 32 0 0 0 0 1 1 1 1 1 1 Llewellyn et al 33 1 1 1 0 1 1 1 0 1 0 Llewellyn et al 34 1 1 1 0 1 1 1 1 1 0 Lu et al 35 0 1 1 0 1 1 1 0 0 0 Maden et al 36 1 0 1 0 1 1 1 0 1 1 Marshall et al 37 0 1 1 0 1 1 1 0 1 0 Mashberg et al 38 0 1 0 0 1 1 1 0 1 1 Merchant et al 39 0 1 0 1 1 1 1 0 1 0 Merletti et al 40 1 1 1 0 1 1 1 0 1 0 Moreno-Lopez et al 41 1 1 1 0 1 1 0 0 1 0 Muscat et al 42 1 1 0 0 1 1 1 1 1 1 Nandakumar et al 43 1 1 0 0 1 1 1 0 1 0 Olshan et al 44 1 1 0 0 1 1 1 1 1 1 Pacella-Norman 45 1 1 0 0 1 1 1 0 1 1 Rao et al 46 1 0 0 0 1 1 1 0 1 1 Rogers et al 47 1 0 1 0 1 1 1 1 1 0 Rosenquist 48 1 1 1 0 1 1 1 1 1 0 Schwartz et al 49 1 1 1 0 1 1 1 0 1 1 Smith et al 50 1 1 0 0 1 1 1 0 1 0 Toporcov et al 51 1 53 1 1 0 1 1 0 1 0 1 1 Zheng et al 54 1 1 0 0 1 1 1 1 1 1 Znaor et al 55 1 0 0 0 1 1 0 1 1 0 A: Expli...…”
Section: Study Characteristicsmentioning
confidence: 99%
“…11,16 Studies in several populations have found that the risk of esophageal SCC (ESCC) is closely associated with genetic polymorphisms of the two alcohol-metabolizing genes, and this relationship has been suggested to be alcohol amount dependent. [17][18][19] Recently, the mutant ALDH2 Glu487Lys allele in molecular epidemiological studies has been reported to be more prevalent among head and neck carcinoma (HNC) patients of a younger diagnosed age (<66 years). 20 Earlier multiple esophageal dysplasias in HNC patients have also been linked to the presence of this variant allele.…”
Section: Uiccmentioning
confidence: 99%